2018
DOI: 10.1016/j.envint.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes and ethanol cook stove intervention: A randomized-controlled trial in Ibadan, Nigeria

Abstract: Transition from traditional biomass/kerosene fuel to ethanol reduced adverse pregnancy outcomes. However, the difference in birthweight was statistically significant only after covariate adjustment and the other significant differences were in tertiary endpoints. Our results are suggestive of a beneficial effect of ethanol use. Larger trials are required to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 41 publications
3
103
1
Order By: Relevance
“…Systematic reviews have linked cleaner cooking fuels with improvements in health (Quansah et al 2017;Thakur et al 2018;WHO 2014c;Pope et al 2017;Bruce et al 2013), but evidence is still not strong, suffers from few well-designed studies, and varies by end point. Intervention studies of chimney stoves or improved solid biomass stoves have provided mixed evidence of health benefits (Sambandam et al 2015;McCracken et al 2007;Thompson et al 2011;Hartinger et al 2013;Tielsch et al 2016;Johnson et al 2013;Mortimer et al 2017;Lee et al 2019;Alexander et al 2018). Evidence from observational studies is moderate for birth weight, pneumonia, and BP and still sparse for stunting.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews have linked cleaner cooking fuels with improvements in health (Quansah et al 2017;Thakur et al 2018;WHO 2014c;Pope et al 2017;Bruce et al 2013), but evidence is still not strong, suffers from few well-designed studies, and varies by end point. Intervention studies of chimney stoves or improved solid biomass stoves have provided mixed evidence of health benefits (Sambandam et al 2015;McCracken et al 2007;Thompson et al 2011;Hartinger et al 2013;Tielsch et al 2016;Johnson et al 2013;Mortimer et al 2017;Lee et al 2019;Alexander et al 2018). Evidence from observational studies is moderate for birth weight, pneumonia, and BP and still sparse for stunting.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…Evidence from observational studies is moderate for birth weight, pneumonia, and BP and still sparse for stunting. Recent trials have shown mixed results from clean cooking fuels, including ethanol and LPG (Alexander et al 2018;Olopade et al 2017;Alexander et al 2017). Taken together, by addressing multiple outcomes at different ages and studying several LMIC contexts, the HAPIN trial is well positioned to fill critical scientific gaps with direct relevance to national policies.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…5 Pregnant women and their young children are especially vulnerable due to the large amount of time spent indoors cooking. 6 These include higher risk of low birthweight, increased stillbirth, 7,8 higher odds of acute lower respiratory infections among children less than five years of age, 9 and higher risk of perinatal mortality, neonatal mortality, and macerated stillbirths. 8,10 Few studies, however, have adequately measured personal exposure to household air pollution because of lack of easy-touse and easy-to-deploy equipment.…”
Section: Introductionmentioning
confidence: 99%
“…6 These include higher risk of low birthweight, increased stillbirth, 7,8 higher odds of acute lower respiratory infections among children less than five years of age, 9 and higher risk of perinatal mortality, neonatal mortality, and macerated stillbirths. 8,10 Few studies, however, have adequately measured personal exposure to household air pollution because of lack of easy-touse and easy-to-deploy equipment. 11,12 In past studies, intention-to-treat analyses lacking personal exposure measurements have led to exposure misclassification and underestimating the true effect of HAP exposure on health outcomes due to stove stacking.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence shows that small reductions in PM2.5 can have benefits in especially vulnerable subpopulations. For example, even a small reduction in PM2.5 can reduce adverse pregnancy outcomes(Alexander et al 2018) and improve growth in children under the age of two years(Lafave et al 2018).…”
mentioning
confidence: 99%